2020
DOI: 10.1371/journal.pone.0230237
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection of the Plagiothecium longisetum Lindb. and proposal of the new species—P. angusticellum

Abstract: Plagiothecium longisetum was described by Lindberg in 1872, based on Maximowicz materials from Japan. In the 1970s, this species was synonymized with P. nemorale. However, a polyphasic approach applied to the investigation of the P. nemorale sensu lato showed a clear separation between the specimens of former P. longisetum and the type of P. nemorale. Morphological features and molecular analyses provide evidence that those two groups are distinct, as well as allowed to describe the new species. The results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 24 publications
3
45
0
3
Order By: Relevance
“…The presence of such a long seta, i.e. up to 5 cm in length, and a long operculum, distinguish the sample from other species of Plagiothecium ; these characteristics, combined with the gametophyte features, are unique to P. longisetum ( Wolski and Nowicka-Krawczyk 2020 ).…”
Section: Plagiothecium Longisetum Accountmentioning
confidence: 95%
See 2 more Smart Citations
“…The presence of such a long seta, i.e. up to 5 cm in length, and a long operculum, distinguish the sample from other species of Plagiothecium ; these characteristics, combined with the gametophyte features, are unique to P. longisetum ( Wolski and Nowicka-Krawczyk 2020 ).…”
Section: Plagiothecium Longisetum Accountmentioning
confidence: 95%
“…The remaining set of features provided by both authors are characteristic of both species: a large plant with a thick turf; loosely arranged and complanate-foliate; large (2.25 mm long and 1.1 mm wide), concave, long-ovate leaves; two costae; an acute to acuminate apex; a developed central strand; thin-wall cells ( Brotherus 1927 ; Iwatsuki 1970 unpubl. ; Wolski 2017 , 2018 , 2020 ; Wolski and Nowicka-Krawczyk 2020 ).…”
Section: Plagiothecium Mauiense Accountmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmed the hypothesis that P. nemorale had previously been too broadly described, and that it should be considered a complex (Wolski, 2017(Wolski, , 2018. These observations were later confirmed by further taxonomic and molecular research (Wolski & Nowicka-Krawczyk, 2020), which found that two groups of specimens distinguished by Wolski (2017Wolski ( , 2018 are in fact two separate species: P. nemorale sensu stricto and P. longisetum Lindb.…”
Section: Introductionmentioning
confidence: 71%
“…Specimens with symmetrical leaves, a denticulate leaf apex, as well as hexagonal and narrowly hexagonal leaf cells no longer than 100 µm in the central part of the leaf were considered P. nemorale sensu stricto. Material with asymmetrical leaves, an entire leaf apex, and elongated hexagonal leaf cells longer than 100 µm but not exceeding 150 µm in the central part of the leaf was classified as P. longisetum (Wolski, 2017(Wolski, , 2018Wolski & Nowicka-Krawczyk, 2020).…”
Section: Methodsmentioning
confidence: 99%